THE SELF ACTUALIZATION OF THE MAIN CHARACTER ’’IN THE PELICAN BRIEF ’’ FILM DIRECTED BY ALAN J. PAKULA - Gaguk Rudianto (Universitas Putera Batam, 2016)
Characteristics of sef actualization are the terms to identify whether a person is categorized into self-actualized person or not. A sef actualized person is a person who is living creatively and fully using his or her potentials to realize his desire for self-fulfillment, namely, to the tendency for him to become actualized in his own potentials. This research is discussing about the characteristics of self-actualization of the main character, Derby Shaw in fulfilling her self-actualization needs in “Pelican Brief” film directed by J. Pakula in 1993. The method of collecting data in this research is qualitative descriptive research where the data are in the form of sentences or utterences from the script of the film and then they are categorized based on the Abraham Maslow theory of personality especially the motives and the characteristic of self-actialization namely 1) An Accurate perception of reality, 2)Independence, Creativity, Spontaneity, 3) Acceptance of themselves and others, 4) A Problem- centered outlook, rather than a centered outlook, 5) Enjoyment of Life, 6) Good Sense of Humor. After they are categorized, they will be explained to find out the characteristic of sef actualization in the film